Race and ethnicity disparities in post-arrest care in Texas. (July 2022) - Huebinger, Ryan; Chavez, Summer; Abella, Benjamin S.; Al-Araji, Rabab; Witkov, Richard; Panczyk, Micah; Villa, Normandy; Bobrow, Bentley
Abstract: Introduction: Post-arrest care is essential to the chain of survival after out-of-hospital cardiac arrest (OHCA). Sparse literature evaluates disparities in post-arrest care. We sought to measure post-arrest care disparities using a statewide OHCA registry. Methods: We evaluated 2014–2020 data in the Texas Cardiac Arrest Registry to Enhance Survival (TX-CARES) and included adult OHCAs surviving to hospital admission. We stratified subjects by race/ethnicity. Outcomes were targeted temperature management (TTM), percutaneous intervention (PCI), early withdrawal of life-sustaining therapies (WLST), survival to discharge, and survival with cerebral performance category (CPC) of 1–2 (considered favorable). We used both multivariable and mixed-effects, logistic regression models to evaluate the association between race/ethnicity and outcomes, adjusting for confounders. We modeled receiving hospital as a random intercept for the mixed-models analysis. Results: We included 8, 363 OHCAs; 3, 916 White, 2, 251 Black, 2, 196 Hispanic/Latino. On multivariable analysis, Black patients had a lower PCI (aOR 0.4, 95% CI 0.3–0.5) and survival with good CPC (aOR 0.6, 95% CI 0.6–0.7). Hispanic/Latino patients had lower TTM (aOR 0.8, 95% CI 0.7–0.9), PCI (aOR 0.6, 95% CI 0.5–0.8), survival (aOR 0.8, 95% CI 0.7–0.9), and survival with good CPC (aOR 0.7, 95% CI 0.6–0.7). However, after adjusting for clustering by receiving hospital, most of the post-arrest care relationships were negated, and Black patients actually had a higher rate of TTM (aOR 1.2, 95% CI 1.1–1.3). Conclusions: Minority OHCA victims experienced disparities in post-arrest care and outcomes. However, adjusting for receiving hospital random-effect largely diminished these findings. Inter-hospital, post-arrest care disparities may exist.